2015
DOI: 10.1111/j.1540-4781.2015.12181.x
|View full text |Cite
|
Sign up to set email alerts
|

Driving Along the Road or Heading for the Village? Conceptual Differences Underlying Motion Event Encoding in French, German, and French–German L2 Users

Abstract: The typological contrast between verb‐ and satellite‐framed languages (Talmy, 1985) has set the basis for many empirical studies on L2 acquisition. The current analysis goes beyond this typology by looking in detail at the conceptualization of the path of motion in a motion event. We take as a starting point the cognitive salience of specific elements of motion events that are relevant when conceptualizing space. When expressing direction in French, specific spatial relations involving the entity in motion (it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 46 publications
3
51
0
7
Order By: Relevance
“…Talmy, 2000). Flecken, Carroll, Weimar, and Von Stutterheim (2015) studied L2 users performing a motion event description task; they found that even though participants performed almost target-like, they displayed increased attention to information that was only relevant to their L1 when preparing to speak in the L2. These findings fit the view that the native language leads to certain routines of information processing (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Talmy, 2000). Flecken, Carroll, Weimar, and Von Stutterheim (2015) studied L2 users performing a motion event description task; they found that even though participants performed almost target-like, they displayed increased attention to information that was only relevant to their L1 when preparing to speak in the L2. These findings fit the view that the native language leads to certain routines of information processing (cf.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 40 years, a large number of cross‐linguistic studies have concerned motion expression and language acquisition in child and adult learners (cf. Athanasopoulos et al, ; Bowerman & Choi, ; Brown, ; Bylund & Athanasopoulos, ; Cadierno, 2004, 2008; Cadierno & Lund, ; Choi & Bowerman, ; Filipović & Vidaković, ; Flecken et al, ; Hendriks & Hickmann, ; Hendriks, Hickmann, & Demagny, ; Hickmann, Bonnet, & Taranne, ; Navarro & Nicoladis, ; Stam, ; Tomczak & Ewert, ). Most of the research is based on Talmy's typology.…”
Section: The Expression Of Path In Motion Eventsmentioning
confidence: 99%
“…In this regard, Slobin () has hypothesized that language patterns acquired in childhood are “resistant to restructuring in adult second language acquisition” (p. 89). A number of empirical studies have investigated this question (e.g., Athanasopoulos et al, ; Brown & Gullberg, , , ; Bylund, ; Bylund & Athanasopoulous, ; Bylund & Jarvis, ; Daller, Treffers–Daller, & Furman, ; Filipović, ; Flecken et al, ; Hendriks & Hickmann, ; Hijazo–Gascón, ; Larrañaga et al, ; Pavlenko & Volynsky, ; Tomczak & Ewert, ; Vulchanova et al, ; Wu, ; for reviews, see Cadierno, , ). The majority of these studies have concentrated on comparisons of speech alone while a few (Brown, , ; Brown & Gullberg, ; Choi & Lantolf, ; Kellerman & van Hoof, ; Lewis, , ; Negueruela et al, ; Özyürek, ; Stam, , , , , ) have looked at gesture in addition to speech, arguing that speech and gesture together provide a more complete picture of learners' thinking for speaking.…”
Section: Introductionmentioning
confidence: 99%